Faktor-Faktor Penyebab Penyalahgunaan Narkotika di Kampung Boncos Jakarta Barat Ditinjau dari Perspektif Kriminologis - Aulia Rohmawati; Rehnalemken Ginting; Sulistyanta (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
Drug abuse is a growing social and criminal problem in Indonesia, including in the Boncos Village area, Palmerah District, West Jakarta, which is known as an area prone to drug distribution and abuse. This study aims to analyze the factors causing drug abuse and the forms of countermeasures implemented in Boncos Village from a criminological perspective. This study uses an empirical legal method with a descriptive qualitative approach. Primary data were obtained through interviews with the Public Relations Officer of the Narcotics Investigation Unit of the West Jakarta Metro Police, the Deputy Head of RT 07 Boncos Village, and the Secretary of the South Kota Bambu Village, while secondary data were obtained through literature studies. The results of the study indicate that drug abuse in Boncos Village is influenced by several main factors, namely economic factors, low education levels, a social environment that is permissive towards drugs, the influence of peer groups, weak social supervision in the community, and dense and difficult to supervise residential conditions. These factors reflect the existence of social disorganization that encourages the development of deviant behavior. Drug control efforts are implemented through criminal and non-criminal approaches. The criminal approach is implemented through raids, arrests, and law enforcement by the police, while the non-criminal approach is implemented through public awareness campaigns about the dangers of narcotics, user rehabilitation, religious activities, community empowerment, and Community-Based Intervention (CBI) programs. This study concludes that drug control in Kampung Boncos cannot rely solely on law enforcement but requires synergy between law enforcement officers, the government, and the community through a comprehensive, sustainable, and community-based approach.